THE USE OF CHEMICAL FERTILIZERS IN ROMANIA'S AGRICULRURE - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN; Valentin ŞERBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the evolution of the surfaces where chemical fertilizers were used, total consumption of fertilizers and the average consumption per surface unit in Romania and also by micro-region of development in order to establish the trends in the use of the fertilizers, and its concentration degree in terms of Herfindahl-Hirschman Index, (HHI), Gini-Struck Index (GSI) and Coefficient of Concentration (CC). The empirical data were collected from National Institute of Statistics for the period 2007-2020. Romania's mineral fertilizer consumption accounts for 5% of the EU total consumption, for which the country is ranked the 7th after France, Germany, Poland, Spain, United Kingdom and Italy. Compared to the EU mean of 77.2 kg Nitrogen fertilizer consumed per ha UAA in the year 2018, Romania applied less than 60 kg, a level which is far away from over 100 kg used by Belgium, Netherlands, Czechia and Denmark. In 2020, the average consumption of mineral fertilizer in Romania reached 98.16 kg/ha, which is still lower than in the Western EU countries. In the year 2020, the average consumption in Romania was exceeded, in the descending order, only by the West, Bucharest-Ilfov, North West and South West Oltenia regions. If in 2007, it was observed an uniform consumption of fertilizers among the eight micro-regions of Romania, in 2020, a slight moderate concentration was noticed in terms of HHI, GSI and CC. The regions with the highest share in mineral fertilizer consumption in Romania, in the decreasing order, are: West, South Muntenia, South West Oltenia, North East, South East and North West regions. The EU policy regarding the sustainable development of agriculture reducing the use of chemical fertilizers for protecting environment, biodiversity and ensuring food safety is welcome, but it has to be adapted to the actual average consumption and also taking into account the local needs of each country regarding the growth of productivity, farmers' income and profit.